4-Coordinated, 14-electron ruthenium(ii) chalcogenolate complexes: synthesis, electronic structure and reactions with PhICl2 and organic azides. Issue 35 (20th August 2019) - Ng, Wai-Ming; Guo, Xueying; Cheung, Wai-Man; So, Yat-Ming; Chong, Man-Chun; Sung, Herman H.-Y.; Williams, Ian D.; Lin, Zhenyang; Leung, Wa-Hung
Abstract : Ru IV hydroxo and tosylimido complexes are synthesized by reactions of [Ru(ER)2 (PPh3 )2 ] (E = S, Se; R = aryl) with PhICl2 and tosyl azide. Abstract : The 4-coordinated Ru II chalcogenolate complexes [Ru(STipp)2 (PPh3 )2 ] (Tipp = 2, 4, 6-triisopropylphenyl, 1 ) and [Ru(SeMes)2 (PPh3 )2 ] (Mes = 2, 4, 6-trimethylphenyl, 2 ) have been synthesized, and their reactions with PhICl2 and organic azides have been studied. Complex2 synthesized from [Ru II (PPh3 )3 Cl2 ] and NaSeMes displays a seesaw structure with P–Ru–P and Se–Ru–Se bond angles of 103.43(13) and 145.26(6)°, respectively. Natural bond order analyses revealed that in each of1 and2, there are two n → σ* (donor–acceptor) π interactions between the chalcogen lone pairs and the Ru–P antibonding molecular orbitals. The calculated second-order perturbation interaction energies of the two interactions for1 (20.5 and 18.3 kcal mol −1 ) are stronger than those of2 (13.6 and 11.0 kcal mol −1 ), suggesting the thiolate ligand (TippS − ) is a stronger π-donor than the selenolate ligand (MesSe − ) with respect to Ru II . Chlorination of1 with PhICl2 afforded the dichloride complex [Ru(STipp)2 Cl2 (PPh3 )] (3 ), which was hydrolyzed to the hydroxo complex [Ru(STipp)2 (OH)Cl(PPh3 )] (4 ) after column chromatography on silica in air. Treatment of4 with HCl and methyl triflate gave3 and [Ru(STipp)2 (OH)(OTf)(PPh3 )] (OTf = triflate, 5 ), respectively. Reactions of1 and2 with p -tolyl azide ( p -tolN3 ) afforded the tetrazene complexes [Ru{N4 ( p -tol)2 }(ER)2 (PPh3 )] (ER = STipp (6 ), SeMes (7 )), whereas that with tosyl azide (TsN3 ) gave the imido complexes [Ru(κ 2 -NTs)(STipp)2 (PPh3 )] (ER = STipp (8 ), SeMes (10 )). The short Ru–Nimido distances in8 [1.883(3) Å] and10 [1.892(2) Å] are indicative of multiple bond character. Treatment of8 with TsN3 afforded the tetrazene complex [Ru(N4 Ts2 )(STipp)2 (PPh3 )] (9 ), but no cycloaddition was found between10 and TsN3 . Nucleophilic attack of the imido ligand in10 with methyl triflate yielded the amido complex [Ru(κ 2 -NMeTs)(SeMes)2 (PPh3 )](OTf) (11 ). The crystal structures of2, 4, 6, and8–11 have been determined.